(untitled) (BIRDEM Medical Journal, 2026)
Background: In the past, Hepatitis B virus (HB) was menace to mankind and was considered a serious global health burden. WHO reported that, HB resulted in an estimated 1.1 million deaths in 2022, mostly from cirrhosis and hepatocellular carcinoma, it could have been prevented by vaccines that are safe, available and effective. Despite the availability of vaccine, 61 million people are reported to be infected in the South-East Asia Region. Many studies have been conducted in Bangladesh but these focused on risk groups such blood donors, Rohingya migrants, health professionals. The aim of this study was to determine the prevalence of hepatitis B and C virus infection among the secondary school children of rural Bangladesh. Methods: This was a cross-sectional study and was conducted from May and June 2024. Three secondary schools of two upazilas were purposively selected, one girl and two boys. All participants were selected randomly from six to ten classes. The participants were tested for hepatitis B virus surface antigen (HBsAg) and anti-HCV using enzyme linked immunosorbent assay (ELISA). The investigations included height, weight, waist and hip girth, body mass index (BMI), waist-to-hip ratio and waist-to-height ratio, as well as blood pressure (BP), fasting blood glucose (FBG) and serum glutamic-pyruvic transaminase (SGPT). Results: Two hundred and fifty students (boys / girls = 165 / 85) participated in three secondary schools. The biophysical characteristics were assessed (mean ± SD, 95% CI) and found that the boys had significantly higher general obesity (BMI P<0.001); central obesity (WHR p<0.001, WHtR p<0.001). The values for FBG (p=0.045) and DBP (p<0.001) were significantly higher in girls than among boys. The prevalence of hepatitis B virus (HBV) was found 0.4% among the secondary school students in this study. No hepatitis C virus (HCV) was detected. Conclusion: The prevalence of HBV was 0.4% and the absence of HCV among secondary school children in rural areas indicates a decline compared to the previous studies. This trend suggests that vaccination coverage for HBV in the rural population has been satisfactorily achieved. The study finding also suggest that elimination of this disease is highly possible. BIRDEM Med J 2026; 16(1): 14-18